Kultura, izobraževanje in paradigma trajnosti - Mlinar, Anton (Teorija in praksa, 2012)
The article discusses the idea of sustainability with regard to the aspects ofculture and education. In this context, the idea of sustainability has not yet seen a wider response. The relationship between sustainability on one hand, and culture and education on the other shows the level of consciousness about the urgent question of man's immediate environment, human/cultural as well as natural. The present frame of reference still strongly depends upon economic and political actors which offer objective measures to evaluate reality. Although it sometimes seems they are also indispensable for understanding the social dimensions of sustainability, we draw attention to the importance of sustainability as a new conceptual knowledge and the relationship between sustainability and the concept of man, especially relative to man's needs and dependence on the world as a network of meanings.This aspect of sustainability is important for the education sphere in a similar way as the deepening of knowledge about man's cultural environment is important for sustainability, especially when it comes to developing suitable terminology. The importance of the new conceptual framework should increase confidence in the possibility of changes in thinkingand behaviour
Keywords: Kultura; Culture; Education; Izobraževanje; Sustainable development; Trajnostni razvoj; Učenje; Learning; Osebni razvoj; Personal development; Paradigm; Paradigma